Comparative hindlimb myology within the family Falconidae - Mosto, María Clelia (2017)
A characteristical feature of a raptors’ hindlimb is their strengthen musculature that aids gripping prey with their sharp talons. To trace specific anatomical modifications it is necessary to study closely related species, with this aim, the myology of the hindlimb of the three subfamilies of Falconidae is explored. For this, a description of a Herpetotherinae member (Micrastur ruficollis) was made for the first time. The hindlimb muscle mass of Polyborinae, Falconinae and Herpetotherinae was compared according to their main function (flexion and extension) on their joints (femur, tibiotarsus, tarsometatarsus and digits). The pattern of Micrastur ruficollis resembles that of the Falconidae except for a few differences towards the development of certain muscles. As it is noteworthy the presence of the second belly of the musculus flexor cruris medialis (unique among birds), its identity will be discussed. Also, Micrastur ruficollis had the highest values of the hindlimb mass. Polyborinae and Falconinae had several differences between each other. The muscles mass of the hip and knee, both flexion and extension, were higher in the Polyborinae, this is in accordance to their more terrestrial habit. Instead, Falconinae had a higher mass in the m. flexor digitorum longus, m. flexor hallucis longus and m. tibialis cranialis, the most important muscles for gripping prey.